Serum IL-33/ST2 Axis Expression in Acute Exacerbations of COPD: Correlation with Pulmonary Function - Wei Y; Ling L; Zhu H; Huang Q (International Journal of COPD)
Yan Wei,1 Liu Ling,1 Hongping Zhu,2 Qinrong Huang1 1Department of Respiratory and Critical Care Medicine, Guangyuan First People’s Hospital, Guangyuan, Sichuan, 628000, People’s Republic of China; 2Department of Cardiovascular, Guangyuan First People’s Hospital, Guangyuan, Sichuan, 628000, People’s Republic of ChinaCorrespondence: Qinrong Huang, Department of respiratory and critical care medicine, Guangyuan First People’s Hospital, Guangyuan, Sichuan, 628000, People’s Republic of China, Email huangqinr0727@163.comBackground:  Chronic obstructive pulmonary disease (COPD) exacerbations significantly contribute to morbidity and mortality. Identifying biomarkers linked to disease severity can enhance COPD management. This study investigates the relationship between serum IL-33 and ST2 levels and reduced pulmonary function during acute exacerbations of COPD (AECOPD).Methods:  We conducted a cross-sectional analysis of 194 AECOPD patients assessing IL-33 and ST2 serum levels and their associations with pulmonary function parameters. Patients were stratified into subgroups by age, gender, and the presence of pulmonary hypertension (PH) to explore differential biomarker impacts.Results:  IL-33 and ST2 levels demonstrated significant inverse correlations with FEV1% predicted (IL-33: r = − 0.561, ST2: r = − 0.545, p < 0.001) and the FEV1/FVC ratio. Logistic regression confirmed IL-33 (OR = 1.32, p < 0.001) and ST2 (OR = 1.29, p < 0.001) was associated with reduced pulmonary function. Subgroup analysis revealed more pronounced associations in older patients (≥ 67 years), males, and those with PH.Conclusion:  IL-33 and ST2 are promising biomarkers for identifying individuals at higher risk of reduced pulmonary function during AECOPD. Their utility is particularly significant in specific demographics, emphasizing the need for integrated biomarker-guided COPD management strategies.Keywords: AECOPD, IL-33, ST2, pulmonary function